2018
DOI: 10.1186/s13098-018-0333-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of mean platelet volume with incident type 2 diabetes mellitus risk: the Dongfeng–Tongji cohort study

Abstract: BackgroundMost of prior studies to demonstrate the association between mean platelet volume (MPV) and type 2 diabetes mellitus (T2DM) risk were cross-sectional design with inconsistent results. In the present prospective cohort study, we aimed to explore the relationship between MPV and incident T2DM risk among a middle-aged and older Chinese population.MethodsThis prospective study included 14,009 individuals derived from the Dongfeng–Tongji cohort which was launched in 2008. A total of 997 incident T2DM pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…MPV can differentiate DM patients from HC at a cutoff value of 9.65fl with a sensitivity of 69.6%, specificity of 67.9%, and with an AUC of 0.747, which was significant. Our finding was in line with studies reported from Turkey [ 35 , 52 , 53 ], India [ 34 , 35 , 54 ], and China [ 55 ]. Several studies suggest that platelet sensitivity in DM patients increases due to the action of the various platelet aggregation inductors including ADP, thrombin, and collagen as well as metabolic abnormalities associated with insulin resistance that affect the functional activity of platelet [ 30 , 42 , 56 ], which could likely result in an alteration of platelet indices in patients with DM.…”
Section: Discussionsupporting
confidence: 93%
“…MPV can differentiate DM patients from HC at a cutoff value of 9.65fl with a sensitivity of 69.6%, specificity of 67.9%, and with an AUC of 0.747, which was significant. Our finding was in line with studies reported from Turkey [ 35 , 52 , 53 ], India [ 34 , 35 , 54 ], and China [ 55 ]. Several studies suggest that platelet sensitivity in DM patients increases due to the action of the various platelet aggregation inductors including ADP, thrombin, and collagen as well as metabolic abnormalities associated with insulin resistance that affect the functional activity of platelet [ 30 , 42 , 56 ], which could likely result in an alteration of platelet indices in patients with DM.…”
Section: Discussionsupporting
confidence: 93%
“…Hypertension, diabetes mellitus, dyslipidemia, coronary artery disease, and smoking habits are among the most important medical pre-conditions and stroke-related comorbidities. Several lines of evidence from the literature suggest that a direct correlation exists between MPV and these traditional cerebrovascular risk factors [55][56][57][58][59][60]. MPV was significantly higher (0.65 fL) in individuals with coronary artery disease and patients with high MPV had 17% higher chance of having cardiovascular events compared to patients with low MPV [61].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in MPV, PDW, and P-LCR is a potential biomarker of an increase in platelet size and reactivity. 5 , 21 , 26 , 27 In hyperglycemic condition, the higher blood glucose level increases the production of glycoproteins and causes non-enzymatic glycation of these proteins on the surface of the platelets, which decrease platelets membrane fluidity and causing hyperactive platelets. 28 , 29 Plasma glucose concentration also directly enhances the activation of the arachidonic acid pathway leads to increased thromboxane A 2 formation which is one of the potent platelet activators and contributes to hyperactivity of platelets in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%